If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-9 + x) = -49 (-9 * 7 + x * 7) = -49 (-63 + 7x) = -49 Solving -63 + 7x = -49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '63' to each side of the equation. -63 + 63 + 7x = -49 + 63 Combine like terms: -63 + 63 = 0 0 + 7x = -49 + 63 7x = -49 + 63 Combine like terms: -49 + 63 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| t^3+2=12 | | 4.2-1.4=1.68-3.5x | | 2(-8-4)=72 | | 2(6x+1)=3x-5 | | 2(4x+2)=84 | | 3-4x=4+x | | e^3x=9 | | 5(5+3x)=160 | | 5+10+4p=9-5 | | 2r^2-2/3r | | 4(-2x+10)=48 | | (5x+8)(7+x)=0 | | 3x-5x+8x=48 | | 5y-y=-16 | | z^10/6 | | 1/3-m/21-1/7 | | -4(7+7x)=-280 | | 3.4-1.08=0.68-5.4x | | 0=2x-x | | -4+6x=4x+16 | | Y-3=-1/3(x-4) | | 14*8*5= | | 3+4y=8y-3 | | 4x^2+3x+42=0 | | n=-3+4x | | -4x+3-3x+2=5x+6 | | 5x+3=69-6x | | x^2-xy-4y^2=-2 | | y+9=5/4 | | X+3=-2x-2 | | Y=2x^2+5x+10 | | Y-6=5(x-3) |